Formulation And In Vitro Characterization Of Sotagliflozin Nanosuspension - Kodipyaka, Ravinder; Chukka, Saritha (Journal of Neonatal Surgery, 2025)
Introduction: Sotagliflozin is a dual sodium-glucose co-transporter 1 as well as 2 (SGLT1 and SGLT2) inhibitor. Sodium-dependent glucose transporter 2 (SGLT2) plays an important role in the regulation of blood glucose. It is indicated to treat type 2 diabetes mellitus. The absolute bioavailability of oral sotagliflozin was approximately 25%. It is classified as BCS class II drug and has limited bioavailability due to poor aqueous solubility. Aim & Objective: The aim of this study was to develop and characterize Sotagliflozin nanosuspension and to compare with a coarse suspension for the enhancement of solubility and bioavailability. Materials & methods: Sotagliflozin nanosuspension was developed by high pressure homogenization. DSC study was conducted to know the drug-excipient compatibility. All other physical characterization studies were conducted. Box Behnken design was employed for the optimization of the formulation. Results & Discussion: The optimized nanoformulation (F6) showing the size, PDI, ZP and assay of 112 ± 1.10 nm, 0.211 ± 0.03, -29.64 ± 1.1 mV, 92.21 ± 0.13% respectively. The optimized formulation was stable for 3 months period at room temperature and refrigerated conditions. Conclusion: Sotagliflozin nanosuspension was developed by using high pressure homogenization method. The optimized sotagliflozin nanosuspension (Run 6) showed smaller particle size, uniform particle size distribution and good zeta potential value